Exploring impact on eating behaviour, exercise and well-being during COVID-19 restrictions in the Netherlands. (1st January 2022) - Dijksterhuis, Garmt B.; van Bergen, Geertje; de Wijk, René A.; Zandstra, Elizabeth H.; Kaneko, Daisuke; Vingerhoeds, Monique
Abstract: Many studies address the effect of the COVID-19 restrictions on food consumption and health, focusing on one or two measurements. Whether or not any effects are permanent or change over a longer period of restrictions has not been assessed in such studies. This study presented a survey containing questions on food consumption, exercise and self-assessed physical and mental health, repeatedly for six times over a 20-week period (July to November 2020) to a representative sample of 258 Dutch consumers. The majority of consumers reported no change in food consumption compared to before the COVID-19 restrictions, two smaller groups report a change to a more, or a less, healthy choice. This trend appears stable over the course of the measurements. The 'healthy changers' seem to couple a healthy and more diverse diet to healthy exercise habits, in contrast to the 'unhealthy changers'. No change was observed in self-assessed physical health over the measurements. Overall a decline in time spent exercising showed, as well as a decline in self-assessed mental health. Clearly a lockdown situation affects food choice, exercise habits and (self-assessed) mental health. The fact that habits are able to suddenly change, for better or for worse, and that a decrease in mental health was reported, suggests that such insights need to be further explored to help individual consumers retain a healthy diet and lifestyle, and governments devise effective public health recommendations.